Linking acoustics and finite‐time Lyapunov exponents reveals areas and mechanisms of krill aggregation within the Gulf of St. Lawrence, eastern Canada. (7th August 2015) - Maps, Frédéric; Plourde, Stéphane; McQuinn, Ian H.; St‐Onge‐Drouin, Simon; Lavoie, Diane; Chassé, Joël; Lesage, Véronique
Abstract: The Gulf of St. Lawrence (GSL) is a feeding ground for several baleen whale species from the North Atlantic, providing them with an abundant supply of krill during their seasonal presence. Krill aggregations are found along the abrupt topography formed by the deep channels, but the dynamics of krill aggregations have not yet been characterized at the scale of the whole GSL. In this study, we combined extensive dual‐frequency acoustic observations of krill and Lagrangian numerical simulations to identify the recurrent areas of krill accumulation in summer and the mesoscale circulation mechanisms responsible for their formation. Throughout the GSL, the topographic forcing of the surface circulation appeared essential in forming convergence zones where observed krill concentrations were systematically higher than average, and within which most of the densest patches were observed. This approach can help in defining the dynamics of the feeding habitat of baleen whales in the GSL, in particular blue and fin whales whose diet is dominated by krill.